INTENSIFICATION OF PRODUCTION PROCESS OF THICK EXTRACT OF MILK THISTLE FRUITS BY ULTRASONIC PROCESSING OF RAW MATERIALS - E. T. Zhilyakova; Z. E. Tsvetkova; D. I. Pisarev; N. N. Boyko; E. Yu. Tymoshenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
The aim. This article is devoted to the intensification of the production process of a thick extract of milk thistle fruits using ultrasonic processing of raw materials. Materials and methods. As an object of the study, the crushed milk thistle fruitss from Penza "Biokor" company were used. As the extractant, an aqueous solution of ethanol 70% vol. was used. For ultrasonic processing of plant materials and extractant, the installation "Bandelin SONOPULS HD 3200" was used, the ultrasound frequency was 20 kHz, the radiator power was 280 W, and the temperature was 25°С. The concentration of the extract was performed using a rotary evaporator RV-10 at the temperature of 60°C and a vacuum of 600-650 Mmhg to a residual moisture content of 25%. Qualitative and quantitative analysis of the thick extract was carried out using spectrophotometry and chromatography. Quantitative analysis of the amount of flavolignans was performed on an SF-56 spectrophotometer. The separation of the flavolignan complex and the quantification of silibinin was performed on a liquid chromatograph "Agilent Technologies 1200 Infinity". Results and discussion. During the study it was found out, that processing of the crushed milk thistle fruits by ultrasound at the soaking stage almost doubles the output of the flavoligan complex from medicinal plant materials. The maximum amount of flavolignans is extracted when the fruits of milk thistle and extractant are processed with ultrasound at the frequency of 20 kHz for 5 minutes. Thus the obtained thick extract of milk thistle fruits in the component composition contains both the target flavolignan complex (87.39%, silibinin - 24.36%), providing the hepatoprotective effect, and flavonoids - chlorogenic acid (1.69%) and dihydroquercetin (10.92%) exhibiting antioxidant activity. It was established that, according to the qualitative composition of flavolignans, the obtained thick extract corresponds to preparations based on milk thistle. Thus, for the first time, the method was proposed for obtaining a thick extract of milk thistle fruits using ultrasonic processing of raw materials and extractant at the soaking stage. The obtained thick extract is proposed to be used as an active pharmaceutical substance for the production of granules based on methionine and milk thistle flavolignans. Conclusion. The results of the experiments allow us to recommend obtaining a thick extract of the milk thistle fruits, using the stage of ultrasonic processing of raw materials and extractant for 5 minutes at the ultrasound frequency of 20 kHz.